45, X/46, XY Mosaicism and Possible Association With Hypothyroidism in Males. (June 2016) - Hojat, Leila; Schweiger, Michelle
Mosaicism has a wide phenotypic spectrum but frequently manifests as the normal male phenotype. Its association with short stature has been well recognized and appears to respond effectively to growth hormone therapy. We present 2 phenotypically normal males who both initially presented with short stature and were found to have hypothyroidism. They were treated for hypothyroidism but their growth did not improve as expected. Further testing revealed 45, X/46, XY mosaicism in both males. We propose that a potential link exists between 45, X/46, XY mosaicism and hypothyroidism, which has not been previously described in the literature. Furthermore, it may be beneficial to evaluate for other disorders such as 45, X/46, XY mosaicism in young males with short stature and hypothyroidism if their growth does not improve once they become euthyroid.